Development and Validation of a Novel Real-time Assay for the Detection and Quantification of Vibrio cholerae - Rashid, Ridwan Bin; Ferdous, Jannatul; Tulsiani, Suhella; Jensen, Peter Kjaer Mackie; Begum, Anowara (Frontiers in Public Health, 2017)
Vibrio cholerae O1 and O139 has been known for its ability to cause epidemics. These strains produce cholera toxin which is the main cause of secretory diarrhea. V. cholerae non-O1 and non-O139 strains are also capable of causing gastroenteritis as well as septicemia and peritonitis. It has been proven that virulence factors such as T6SS, hapA, rtxA, and hlyA are present in almost all V. cholerae strains. It is imperative that viable but non-culturable cells of V. cholerae are also detected since they are also known to cause diarrhea. Thus, the aim of this study was to develop an assay that detects all V. cholerae regardless of their serotype, culturable state, and virulence genes present, by targeting the species specific conserved ompW sequence. The developed assay meets these goals with 100% specificity and is capable of detecting as low as 5.46 copy number of V. cholerae. Detection is rapid since neither lengthy incubation period nor electrophoresis is required. The assay had excellent repeatability (CV%: 0.24–1.32) and remarkable reproducibility (CV%: 1.08–3.7). Amplification efficiencies in the 89–100% range were observed. The assay is more economical than Taqman-based multiplex real-time PCR assays. Compared to other real-time assays, the ompW assay is specific and sensitive, has better repeatability and reproducibility, and is more economical.